Alterations in cerebral metabolomics and proteomic expression during sepsis - Hinkelbein, Jochen; Feldmann, Robert Enrico; Peterka, Anna; Schubert, Charlotte; Schelshorn, Dominik W.; Maurer, Martin H.; Kalenka, Armin (Current neurovascular research, 2007)
The cause of brain dysfunction during sepsis and septic encephalopathy is still under ongoing research. Sepsis induced changes in cerebral protein expression may play a significant role in the understanding of septic encephalopathy. The aim of the present study was to explore cerebral proteome alterations in septic rats. Fifty-six male Wistar rats were randomly assigned to a sepsis group (coecal ligature and puncture, CLP) or a control group (sham). Surviving rats were killed 24 or 48 hours after surgery and whole-brain lysates were used for two-dimensional gel electrophoresis and subsequent protein identification. Differentially expressed proteins were identified by mass spectrometry. Using the Ingenuity Pathways Analysis (IPA) tool, the relationship and interaction between the identified proteins was analyzed. Mortality was 53 % in septic rats. No rat of the control group was lost. More than 1,100 spots per gel were discriminated of which 29 different proteins were significantly (2-fold, P < 0.01) changed: 24 proteins down-regulated after 24 hours; two proteins up-regulated and three down-regulated after 48 hours. IPA identified 11 of 35 differentially regulated proteins allocating them to an existing inflammatory pathway. In the analysis of septic rat brains, multiple differentially expressed proteins associated with metabolism, signaling, and cell stress can be identified via proteome analysis, that may help to understand the development of septic encephalopathy.